Creating a system of medical and psychological rehabilitation of extreme professions representatives (firemen-rescuers as a model) - J. Chumaeva; V. Golikovа; J. Nekhoroshkova; A. Ogulenko; L. Shafran (Journal of Education, Health and Sport, 2015)
Chumaeva Julia, Golikovа Vladislava, Nekhoroshkova Julia, Ogulenko Alexey, Shafran Leonid. Creating a system of medical and psychological rehabilitation of extreme professions representatives (firemen-rescuers as a model). Journal of Education, Health and Sport. 2015;5(8):197-209. ISSN 2391-8306. DOI 10.5281/zenodo.28064